2020
DOI: 10.1155/2020/8824091
|View full text |Cite
|
Sign up to set email alerts
|

Research on an Improved Metal Surface Defect Detection Sensor Based on a 3D RFID Tag Antenna

Abstract: Structural health monitoring (SHM) technology is a monitoring process and early warning method for the health status or damage of special workpiece structures by deploying sensors. In recent years, there have been many studies on SHM, such as ultrasonic, pulsed eddy current, optical fiber, magnetic powder, and other nondestructive testing technologies. Due to their sensor deployment, testing environment, power supply, and transmission line wiring mechanism, they bring problems such as detection efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In [50], a multi-directional expansion of metal defects is studied, where a 3D patchbend dipole operating at 915 MHz was used. The simulation process was performed via Ansys HFSS.…”
Section: Figurementioning
confidence: 99%
“…In [50], a multi-directional expansion of metal defects is studied, where a 3D patchbend dipole operating at 915 MHz was used. The simulation process was performed via Ansys HFSS.…”
Section: Figurementioning
confidence: 99%
“…Literature [20] tested the performance of a sensor integrating wireless sensing technology and intelligent monitoring technology for workpiece structure identification based on simulation experiments and found that this sensor accurately identifies and locates workpiece defects. Literature [21] confirms the good performance of the metal defect identification system based on graphical alignment algorithms and defect identification module through the feedback from the use of the metal defect identification system in three real cases, which can achieve the goal of accurately locating the position of metal defects.…”
Section: Introductionmentioning
confidence: 99%
“…The number, degree, and distribution of surface defects areas are significant factors to determine the quality of industrial metal planar materials. The damage detection methods based on vibro-acoustic modulation [ 1 ], wireless sensing technology [ 2 ] and other different principles have been researched for a long time. However, the computer-vision-based surface defect detection methods are the most commonly used to find and locate the abnormal areas on the image surface due to their advantages of low cost, easy operation, and superior performance, etc.…”
Section: Introductionmentioning
confidence: 99%